Perkembangan Kurikulum Pendidikan Agama Islam Di Indonesia (Telaah Kurikulum PAI Pra Kemerdekaan hingga Kurikulum Merdeka) - Zulkifli, Zulkifli; Muhammad, Muhammad (Prodi Pendidikan Agama Islam IAINU Kebumen, 2023)
This study aims to describe the development of the Islamic Religious Education (PAI) curriculum in Indonesia, with a focus on the development of the Pre-Independence, Old Order, New Order, and Reform Era to the Independent Curriculums. This research uses the library research method. Data collection was carried out using documentation study techniques. The results of this study indicate that Islamic Religious Education (PAI) is experiencing dynamics of development in line with the government's political attitude towards Muslims. Entering the end of the New Order era to the current reform era, Islamic religious education is experiencing positive developments, it's just that the curriculum still has to be designed to be compatible with the dynamics of the times.